PERANG DINGIN ANTARA AMERIKA SERIKAT DAN UNI SOVIET : KAJIAN ANALISIS BUKU TEKS PELAJARAN SEJARAH SMA - Syafarudin, Nur; Suhartati Saputri, Ema (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
Textbooks as a learning resource whose content provides historical knowledge about historical events including the background of the Cold War. The problem is to reveal the background of the cold war between the United States and the Soviet Union in a history textbook, based on a study in the 2006 edition of the high school history textbook. Qualitative research methods by applying literature review research focused on the 2006 edition of the high school history textbook and other additional sources. As for the data analysis technique, Teun A. van Dijk applies three dimensions, namely text, social cognition, and superstructure. The findings show that in the 2006 edition of the high school history textbook, various causes of the cold war were found, namely, ideological clashes and power struggles, and also forms of the cold war were found. In the political field, the two countries implemented different systems of government, the economic sectors of the United States and the Soviet Union competed with each other by attracting other countries, the military sectors of the two countries strengthened each other's defenses, and in the space sector, the systems in space experienced sophistication. It can be concluded that this Cold War provided competition in various fields between the United States and the Soviet Union, including politics, economics, military and space.